Pelatihan Penyusunan Ransum Sapi Potong Berbasis Limbah Pertanian di Kecamatan Kuok Kabupaten Kampar - Novita, Maulina; Ramdani, Dedi; Habiyah, Umul; Hidayat, Rahmat; Prahadi Nata, Aldi (Journal of Social and Community Service, 2024)
Feed is one of the important factors that must be considered in raising livestock. The success of raising livestock is determined by the quality of the feed provided. However, there are still many breeders who do not pay attention to the quality of the feed given to their livestock, resulting in less than optimal growth and productivity. Lack of public knowledge about livestock and planning causes large costs incurred by livestock farmers. Therefore, it is necessary to provide training and education to the community so that the costs incurred in raising livestock can be reduced. SMK Negeri 1 Kuok is the only Vocational High School where one of the student's Skill Competencies is Ruminant Agribusiness. Students at SMK Negeri 1 Kuok, especially the Ruminant Agribusiness Skills Competency, as young livestock people who will later take part in society, should be equipped with special skills that they can later apply in society. This community service activity aims to provide training to the community in producing alternative feed products and improving the quality of animal feed products which is currently a problem for partners. This service includes workshop activities providing material on animal feed processing by utilizing appropriate technology and environmentally friendly methods for community empowerment. To increase the productivity of livestock, it needs to be supported by adequate feed with nutritional requirements that are met. Therefore, farmers need to have sufficient knowledge and understanding to be able to process good and highly nutritious animal feed to support the productivity of their livestock. So this training makes a positive contribution to partners. The response of training participants to the implementation of Community Partnership Program activities was in the good category.